HUBUNGAN LINGKUNGAN BELAJAR VIRTUAL TERHADAP PENDEKATAN BELAJAR MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN AJARAN 2020/2021 SELAMA PANDEMI COVID-19 - Fellicia Naurah Andryas (2021)
The ongoing COVID-19 pandemic has bestowed upon the global citizens what is now known as the new normal. The Ministry of Education and Culture of Indonesia has acted accordingly by ordering every academic institution to practice online learning to lower the transmission of the SARS-COV-2 virus. This abrupt pedagogical transformation poses a new challenge for both students and teachers. Consequently, continuous monitoring and evaluation of the study process are essential to maintain high quality education. This research aims to illustrate the perception of student's experienced virtual learning environment (VLE), chosen learning approach, and the association between them. A cross-sectional design was chosen for this study. Participants (n=210) currently registered as pre-clinical undergraduate medical students in Universitas Pembangunan Nasional Veteran Jakarta during the 2020/2021 academic year were asked to complete an online survey. Online Learning Environment Survey (OLES) and Revised Study Process Questionnaire 2 Factors (R-SPQ-2F) are used to determine VLE effectiveness and learning approach, respectively. 99% (n=208) of the students perceive their VLE as highly effective and 88,6% (n=186) use the deep learning approach. Fisher's Exact Test revealed a significant correlation between perceived VLE and the learning approach (p=0,013). An effective VLE is of paramount importance as it influences students' approach to learning during their study process.